Effect of cements on fracture resistance of monolithic zirconia crowns - Keisuke Nakamura; Mathieu Mouhat; John Magnus Nergård; Solveig Jenssen Lægreid; Taro Kanno; Percy Milleding; Ulf Örtengren (Acta Biomaterialia Odontologica Scandinavica, 2016)
Objectives The present study investigated the effect of cements on fracture resistance of monolithic zirconia crowns in relation to their compressive strength. Materials and methods Four different cements were tested: zinc phosphate cement (ZPC), glass-ionomer cement (GIC), self-adhesive resin-based cement (SRC) and resin-based cement (RC). RC was used in both dual cure mode (RC-D) and chemical cure mode (RC-C). First, the compressive strength of each cement was tested according to a standard (ISO 9917-1:2004). Second, load-to-failure test was performed to analyze the crown fracture resistance. CAD/CAM-produced monolithic zirconia crowns with a minimal thickness of 0.5 mm were prepared and cemented to dies with each cement. The crown–die samples were loaded until fracture. Results The compressive strength of SRC, RC-D and RC-C was significantly higher than those of ZPC and GIC (p < 0.05). However, there was no significant difference in the fracture load of the crown between the groups. Conclusion The values achieved in the load-to-failure test suggest that monolithic zirconia crowns with a minimal thickness of 0.5 mm may have good resistance against fracture regardless of types of cements.